(untitled) (Research, Society and Development, 2020)
This work is the result of concerns raised in our trajectory as teachers and researchers in the field of literacy and literacy for children and adolescents. It is a methodological exercise to assist in the apprehension and, pari passu, in the comprehension of the programmatic contents pertinent to teacher training, having as a propositional way the task of correlating the following categories: thought and language; literacy methods; literacy and literacy; reading; and reading strategies in the child development process with regard to the acquisition of literacy. We use the bibliographic approach as a methodological resource, from which we analyze authors dealing with the aforementioned theme, being also appreciated under the prism of the basic works of the educational praxis of historical-critical pedagogy. We emphasize that the categories that were presented briefly and briefly in this study, despite being exposed separately, only make sense if they are interpreted together, because, due to their inextricable overlap, and their intertwining that they require for the achievement of labor educational, none of these categories can be properly understood if considered in isolation.